SARS-CoV-2 B.1.1.529 (Omicron) Variant Causes an Unprecedented Surge in Children Hospitalizations and Distinct Clinical Presentation Compared to the SARS-CoV-2 B.1.617.2 (Delta) Variant - Taytard, Jessica; Prevost, Blandine; Schnuriger, Aurélie; Aubertin, Guillaume; Berdah, Laura; Bitton, Lauren; Dupond-Athenor, Audrey; Thouvenin, Guillaume; Nathan, Nadia; Corvol, Harriet (Frontiers in Pediatrics, 2022)
Background In the midst of successive waves of SARS-CoV-2 variants, the B.1.1.529 (omicron) variant has recently caused a surge in pediatric infections and hospitalizations. This study aimed to describe and compare the symptoms, explorations, treatment and evolution of COVID-19 in hospitalized children during the successive B.1.617.2 (delta) and B.1.1.529 (omicron) waves. Methods This observational study was performed in the Pediatric Pulmonology Department of a University Hospital in Paris, France. All hospitalized children aged between 0 and 18 years who tested positive for SARS-CoV-2 using reverse transcription polymerase chain reaction (RT-PCR) in nasopharyngeal swabs from July 15th to December 15th 2021 (delta wave), and from December 15th 2021 to February 28th 2022 (omicron wave) were included. Results In total, 53 children were included, 14 (26.4%) during the delta wave and 39 (73.6%) during the omicron wave (almost three times as many hospitalizations in half the time during the latter wave). During the omicron wave, hospitalized patients were mostly aged < 5 years (90 vs. 71% of all the children during omicron and delta waves, respectively), and tended to have fewer underlying conditions (56 vs. 79% during omicron and delta waves, respectively, p = 0.20). The omicron variant was also responsible for a different clinical presentation when compared to the delta variant, with significantly higher and often poorly tolerated temperatures (p = 0.03) and increased digestive symptoms (p = 0.01). None of the three patients who were older than 12 years were fully vaccinated. Conclusion The dramatic increase in the hospitalization of children with COVID-19 and the modification of the clinical presentation between the latest delta and omicron waves require pediatricians to remain vigilant. It should also encourage caregivers to ensure vaccination in children older than 5 years, for whom the BNT162b2 COVID-19 vaccine has been deemed safe, immunogenic, and effective.